52.4k views
1 vote
Factor Completely.
12k^2-16k-60

2 Answers

4 votes

Answer:

4(k - 3)(3k + 5)

Explanation:

Given

12k² - 16k - 60 ← factor out 4 from each term

= 4(3k² - 4k - 15) ← factor the quadratic

Consider the factors of the product of the coefficient of the k² term and the constant term which sum to give the coefficient of the k term

product = 3 × - 15 = - 45 , sum = - 4

Factors are - 9 and + 5

Use these factors to split the middle term

3k² - 9k + 5k - 15 → ( factor the first/second and third/fourth terms

= 3k(k - 3) + 5(k - 3) ← factor out (k - 3)

= (k - 3)(3k + 5)

Hence

12k² - 16k - 60 = 4(k - 3)(3k + 5) ← in factored form

User Multicollinearity
by
5.1k points
2 votes

Hey there!


  • \bold{Factoring:}
    \bold{12k^2-16k-60}

  • \bold{Solving\downarrow}

  • \boxed{\boxed{\bold{Answer:4(3k+5)(k−3)}}}


  • \bold{Check\downarrow}

  • \bold{4(3k+5)(k-3)}

  • \bold{4*3k=12k}

  • \bold{4*5=20}

  • \bold{4*k=4k}

  • \bold{4*-3=-12}
  • Combine your like terms and that should lead us to the equation we have now
  • So, this makes our result true:
    \boxed{\boxed{\bold{Answer:4(3k+5)(k-3))}}}
    \checkmark

Good luck on your assignment and enjoy your day! |

~
\bold{LoveYourselfFirst:)}

User W A K A L E Y
by
5.4k points